Dreaming High Through Education: Theme Analysis of Educational Values Identified in ‘Laskar Pelangi’ - Santosa Santosa; Radik Darmawan; Zaenal Abidin (Jurnal Pendidikan Bahasa, 2023)
The present study aimed at identifying the college students’ perceptions toward the main characters depicted in Andrea Hiratas’ novel entitled ‘Laskar Pelangi’. Qualitative method was used to describe the students’ verbal perceptions toward the above-mentioned novel. Eight respondents were assigned to read the novel for two weeks, and further interviewed in semi-structured manner. The findings indicated that there were some important values, which could probably contribute to the main characters’ success, such as being grateful, religious, and motivated. Furthermore, it was also found that the success experienced by the main characters were not only an inner-driven matter. In fact, the other externally driven factors might have significantly contributed to their success, such as parents and teachers’ contributions, which should have been described more in the novel. Given with the current gloomy economic situation, the students’ attempts to accomplish their goals are perceived more difficult to be materialized as numerous intertwined factors might hamper the students’ expensive dream.